The Matlab toolbox for modeling complex mechanisms - Pająk, Iwona (Zielona Góra: Uniwersytet Zielonogórski)
In the paper, a new version of the Matlab toolbox for modeling and simulation of any mechanisms consisting of open kinematic chains is presented. This tool renders it possible to define any manipulator described by Denavit-Hartenberg parameters and then connect the mechanisms created in this way into one complex mechanism. The package can be used for a realistic visualization of robot motion necessary in research, didactic process or during design of a production cell. Available functions render it possible to show a realistic model of a mechanism based on both default and user defined appearance. The toolbox also provides a set of tools for performing simultaneous simulations of many robots and other objects in their workspace. An example illustrating new features of the toolbox, presenting modeling and motion simulating of human upper limb is also attached.
Keywords: robot toolbox; robot modeling; simulation; Matlab